Changes in psychosocial wellbeing over a five-year period in two predominantly Black Pittsburgh neighbourhoods: A comparison between gentrifying and non-gentrifying census tracts. (May 2023) - Mendoza-Graf, Alexandra; Collins, Rebecca L; Dastidar, Madhumita Ghosh; Beckman, Robin; Hunter, Gerald P; Troxel, Wendy M; Dubowitz, Tamara
Gentrification often leads to changes within urban neighbourhoods. While redevelopment and investment may improve the built environment in gentrifying neighbourhoods, there may be disruptive impacts that affect health and wellbeing for existing residents. A growing body of literature explores the impact of gentrification on the psychosocial wellbeing of residents. This study sought to understand gentrification's effects on three aspects of psychosocial wellbeing in a random sample of predominantly Black residents in two neighbourhoods in Pittsburgh, Pennsylvania ( n  = 662). Residents were enrolled in 2011 and surveyed multiple times through 2018. We used American Community Survey data to create a tract-level measure of gentrification to categorise the 13 census tracts in the two neighbourhoods as gentrified or not gentrified between 2011 and 2018 and assessed whether gentrified tracts experienced predominantly White or Black gentrification. We then estimated multivariate regression models to test associations between gentrification status and participant-level changes in perceived neighbourhood social cohesion, neighbourhood satisfaction and psychological distress, between 2013 and 2018. Relative to participants living in non-gentrified tracts, we found those living in gentrified tracts (all of which were Black gentrified) experienced smaller improvements in perceived neighbourhood social cohesion (coef.  =−0.21, p  = 0.005) and neighbourhood satisfaction (d y /d x  = 0.12, p  = 0.003). We found no statistically significant association between gentrification and changes in psychological distress. These results suggest that although gentrification may bring about needed resources in the community, further consideration should be given to help ensure any detrimental effects on social cohesion and neighbourhood satisfaction are mitigated.